An Analysis of Slang Words and Phrases in the Dialogues of Monsters University - Dhanika Vidyadhari (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2026)
Slang constitutes an important linguistic feature in American popular culture. In informal interaction, slang often functions more effectively than standard or conventional English because it allows speakers to express intimacy, solidarity, humour, and group identity. This study aims to identify and classify the characteristics of slang words and phrases found in the dialogues of the film Monsters University (2013), associated with Dan Scanlon, Dan Gerson, and Robert L. Baird. This research employed a qualitative method with a descriptive approach. The data source was the movie script of Monsters University (2013), while the data consisted of slang words and phrases occurring in the characters' dialogues. The procedures of data analysis involved observation, identification, classification, description, and conclusion drawing. The analysis was based on Andersson and Trudgill's (1990) classification of slang characteristics, namely neutral syntax, informal situation, spoken language, and creativity. The findings show that 32 slang items were identified in the film. These items consist of 9 words or phrases categorized as neutral syntax, 11 words or phrases categorized as informal situation, 7 words or phrases categorized as spoken language, and 5 words or phrases categorized as creative forms. These findings indicate that slang in animated film dialogue contributes to the construction of natural, humorous, and youth-oriented interaction, while also strengthening characterization and social identity among speakers.. Key Words: slang, American slang, sociolinguistics, film dialogue, Monsters University